COMMODITY SCIENCE WITHIN THE FRAMEWORK OF TRADE ACTIVITIES IN POST-WAR UKRAINE - Ільчук, Микола; Кириченко, Анастасія; Томашевська, Ольга (SWorldJournal, 2025)
The article examines the role of commodity science in restoring Ukraine’s trade activities in the post-war period. It analyzes the theoretical and methodological foundations of commodity science, its functions in shaping assortments and ensuring product